Effect of lower and upper body high intensity training on genes associated with cellular stress response - Zychowska, M.; Kochanowicz, A.; Kochanowicz, K.; Mieszkowski, J.; Niespodzinski, B.; Sawczyn, S. (BioMed Research International, 2017)
This study aimed to compare the effect of upper and lower body high intensity exercise (HIE) on select gene expression in athletes. Fourteen elite male artistic gymnasts (age years; weight kg; fat free mass kg; height m) performed lower and upper body 30 s Wingate Tests (WAnTs) before and after eight weeks of specific HIIT. Two milliliters of blood was collected before and after (5, 30 min, resp.) lower and upper body WAnTs, and select gene expression was determined by PCR. Eight weeks of HIIT caused a significant increase in maximal power (722 to 751 Wat), relative peak power in the lower body WAnTs (10.1 to 11 W/kg), mean power (444 to 464 W), and relative mean power (6.5 to 6.8 W/kg). No significant differences in lower versus upper body gene expression were detected after HIIT, and a significant decrease in the IL6/IL10 ratio was observed after lower (-2 0.57 ) and upper (-2 0.5 ) WAnTs following eight weeks of HIIT. It is hypothesized that a similar adaptive response to exercise may be obtained by lower and upper body exercise.